Synergistic Action of PGPR and Biofungicide with Active Ingredient of Cladosporium clasporioides to Control White Rust on Chrysanthemum - Wakiah Nuryani; Hanudin Hanudin; Indijarto Budi Rahardjo; Kurniawan Budiarto (Faculty of Agriculture University of Brawijaya in collaboration with PERAGI, 2022)
The application of antagonist microbes to control significant diseases on crops is an essential issue in the eco-friendly and sustainable agriculture of the chrysanthemum production system. The application of antagonist consortiums is expected to synergistically suppress the pathogen more effectively than a single microbe, thus increasing the marketable flower yield. The research is carried out to evaluate the single and combined application of antagonists C. ladosporioides and PGPRs, B. subtilis, and P. flourescens to control white rust in Chrysanthemum. The results show that there is no cumulative effect from the combination of biofungicide and the PGPR on disease suppression, disease incidence, and plant growth improvement than single antagonist treatments. Compared to synthetic fungicide, biofungicide and the PGPR treatments give higher parasitism intensity, though the values were negligible among the treatments. The lowest disease intensity is recorded from synthetic fungicide treatment. The improvement of flower quality due to biofungicide, PGPR, and synthetic fungicide treatments was found only on the longer vase life than untreated plants. Observation on the compatibility of antagonists with PGPRs are still needed to increase the effectiveness in controlling white rust in Chrysanthemum.